Canonical and non-canonical clitic placement in free word order language - Peti-Stantić, Anita (2012)
The general claim in the past has been that in free word order languages, such as South Slavic languages, the distribution of clitics is bound to the positions that depend on either syntactic or phonological constraints. My research demonstrates that the clitic placement in South Slavic languages allows for much more freedom than was previously claimed in the literature. Although the first task seems to be factoring out the ungrammatical sequences, especially as a lot of disagreement arose in linguistic literature over that question, this task showed to rely heavily on factors that were not accounted for by now. Since the distribution of clitics relies on fine-grained interplay between different components of grammar, it is important to determine types of constraints that play role in clitic placement, as well as their hierarchy, at the same time accounting for some variables that were never tested in order to gain information on grammaticality/acceptability and/or the dynamics of processing. To counterbalance the claims that were not supported by testable data, I am conducting the set of judgment task experiments (partially using ME method), as well as the paraphrasing and contrastive sentence completion experiments. My main goal is to explore the difference in non-controversially grammatical and what has been claimed to be ungrammatical linguistic data. My prediction is that the acquisition of the latter is delayed, or even suspended, depending on various factors I will be controlling for. While designing the experiment, I accounted for three types of constraints and their combinations: 1. phonological, 2. morphosyntactic, and 3. informational. At the same time I controlled for the age, level of education, reading habits, and exposure to the linguistic analysis. Based on the systematization of results, I propose that the relevant discrimination line be set up between sequences with canonical and non-canonical clitic placements rather than the grammatical and ungrammatical ones. Sequences with canonical clitic placements exhibit perfect match between prosodic and syntactic phrasing (Ex. 1.1, 2.1 and 3.1), and these sentences require basic semantic reading. Sequences with non-canonical clitic placements do not exhibit perfect match between prosodic and syntactic phrasing (Ex. 1.2, 3.4, 3.5), and the appropriate reading for these sentences requires alternative semantic interpretations that rely on focus marking. The main goal of this study is to demonstrate that the experimental investigation of clitic placement is best couched in the domain of gradience. Such an approach, by offering novel evidence for acceptability of the sequences that are claimed to be ungrammatical, advances linguistic theory by uncovering acceptability distinctions that have gone unnoticed in the literature up to the present day. Since the experiments have already confirmed that hierarchy of constraints plays substantial role in the language acquisition, but that the “external” factors also play a role in acquisition dynamics, this discovery not only results in a significant contribution to our understanding of the interface between phonological, morphosyntactic and information structures in free word order languages, but also opens a new path for investigation of acquisition of complex linguistic data.